Consumption paths under prospect utility in an optimal growth model - Reto Foellmi; Rina Rosenblatt-Wisch; Klaus Reiner Schenk-Hoppé (University of Bern, Department of Economics, 2010)
This paper studies the Cass-Koopmans-Ramsey model of optimal economic growth in the presence of loss aversion and habit formation. The representative agent's preferences for consumption can be gradually varied between the standard constant intertemporal elasticity of substitution (CIES) case and Kahneman and Tversky's prospect utility. We find that the transitional dynamics of optimal consumption paths differ distinctly from the standard model, in particular consumption smoothing is more pronounced. We also show that prospect utility can cause the economy to remain in a steady state with low consumption and low capital.
Keywords: E21; O41; 330; Ramsey growth model; prospect theory; loss aversion; optimal consumption; Optimales Wachstum; Prospect Theory; Risikoaversion; Erwartungsnutzen; Optimaler Konsum; Substitutionselastizität; Steady-State-Wachstum; Theorie